Brand Authenticity in Healthcare - Victorino, Guilherme (2013)
Victorino, G. (2013). Brand Authenticity in Healthcare: conceptualizing authenticity in the private hospital market [abstract]. In 3rd International Consumer Brand Relationship Colloquium Proceeding (pp. 1-32). Rollins College.